Pengaruh Kemandirian Belajar Terhadap Hasil Belajar Matematika Siswa Kelas VIII SMP - Maya Fitria Ningsih; Ketut Sarjana; Syahrul Azmi; Baidowi Baidowi (Pendidikan Matematika FKIP Universitas Mataram, 2021)
Purpose of this research is to know influence of learning independence on student mathematic study result in VIII grade in SMP Negeri 9 Mataram academic year 2020/2021. Types of research is Causal comparative Quantitative research or ex-post facto. The sample was selected using simple random sampling technique, obtained 39 students were taken 4 or 5 students from each class randomly spread over 8 classes in class VIII SMP Negeri 9 Mataram. Data collection in this study was carried out by providing a learning independence questionnaire in the research sample and documentation of mid-semester test scores obtained from mathematics subject teachers. The results showed that there was a positive correlation between learning independence and learning result, namely α = 0.610. With the other catalyst, the correlation was in the strong category. The amount of the contribution of learning independence to the mathematics learning result of class VIII students of SMP Negeri 9 Mataram academic year 2020/2021 is 37.20% and this is quite significant at the 0.05 significant level. This result can also be shown by the regression equation Y = 19.187 + 0.523X where Y is the learning independence and X is the result of learning mathematics.